The role of research ethics committees: Friend or foe in educational research? An exploratory study. (13th July 2020) - Brown, Carol; Spiro, Jane; Quinton, Sarah
Abstract : Ethics committees have an important role to play in ensuring ethical standards (e.g. BERA, ESRC, RCUK recommendations) are met by educational researchers. Balancing obligations to participants, society, institutions and the researchers themselves is not, however, easy. Researchers often experience the ethics committee as unsympathetic to their research endeavour, whilst ethics committees find some research approaches do not make ethical implications sufficiently explicit. This potential for misunderstanding is evident in the literature, but studies investigating how participants perceive this relationship are missing. This research comprises a novel empirical study which explores researcher perceptions of research ethics committees. Fifty‐five participants in higher education departments of education responded to an online survey. Open and closed‐ended questions were used to collect data on roles, methodological stance, experiences of the research ethics committee, perceived tensions and examples of good practice. The results indicated that contemporary educational researchers regard research ethics committees as friends when researcher and reviewer are transparently engaged in a shared endeavour. When this shared endeavour breaks down, for a variety of reasons—including apparently unreasonable demands or mutual misunderstanding—the research ethics committees can become foes. The difference between foe and friend lies in the quality of communication, clear systems and a culture of respectful mutual learning. The contributions of this study have practical implications for the ways that education researchers and research ethics committees relate to one another within university settings, both to alleviate areas of tension and to arrive at a shared understanding which will enable best ethical research practice.